Recommendations for standard criteria for the positional and morphological evaluation of temporomandibular joint osseous structures using cone-beam CT: a systematic review - Abeer A. Almashraqi (12411222) (2023)
Objective This systematic review aimed to appraise the reliability and comprehensiveness of imaging methods in studies that used three-dimensional assessment of the temporomandibular joint (TMJ) in order to propose a standardized imaging method. Methods Six databases/search engines were searched up until September 2022. The outcomes of interest included measurements of the mandibular condyle, glenoid fossa, joint spaces, or the entire TMJ. Two checklists were utilized: one to assess the risk of bias, with a maximum score of 37, and the other, a pre-designed checklist consisting of 22 items to evaluate the comprehensiveness of the methods used, with a maximum score of 33. Results Out of the 2567 records retrieved, only 14 studies, which used cone bean computed tomography (CBCT), were deemed eligible and thus included in the qualitative analysis. Three studies were deemed of low risk of bias, while the remaining studies were rated as moderate to high risk of bias, primarily due to improper reporting of inter-observer agreement, varying reliability values, and a limited number of cases included in the reliability analysis. Regarding the comprehensiveness of the methods used, only four studies achieved relatively high scores. The deficiencies observed were related to the reporting of variables such as slice thickness and voxel size, absence of or improper reporting of intra- and inter-examiner reliability analyses, and failure to assess all osseous components of the TMJ. Conclusion CBCT-based methods used to assess the positions and morphology of TMJ bony structures appear to be imperfect and lacking in comprehensiveness. Hence, criteria for a standardized assessment method of these TMJ structures are proposed. Clinical relevance statement Accurately, comprehensively, and reliably assessing the osseous structures of the temporomandibular joint will provide valid and valuable diagnostic features of the normal temporomandibular joint, and help establish potential associations between these osseous features and temporomandibular disorders. Registration The protocol for this systematic review was registered at the International Prospective Register of Systematic Reviews (PROSPERO, No.: CRD42020199792). Key Points Although many methods have been introduced to assess the osseous structure of the temporomandibular joint, they yielded inconsistent findings. None of the published studies comprehensively assessed the temporomandibular joint. Recommendations for a comprehensive temporomandibular joint osseous assessment method were suggested for better validity and reliability of future research. Other Information Published in: European Radiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00330-023-10248-4